ANALISIS KINERJA KEUANGAN DITINJAU DARI SEGI LIKUIDITAS DAN SOLVABILITAS PADA PT. BANK SULSEL CABANG MAKASSAR - ST. Maryani (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
Financial ratio is a measure that can explain or give an overview to the analyzer of good or bad things are or the financial position of a company, especially if the ratio is compared with the comparable ratio is used as a standard. The level of financial performance of the liquidity ratio appears that in the last 2 years this has increased. An increase in the liquidity ratio, in the last 2 years because of the decline was due to the company's current debt. The level of financial performance of the ratio solvabilitasbahwa circumstances and financial position have demonstrated liquidity position, it can be seen through the analysis of liquidity, which in a span of 2 years increased, this is due to the decreased current liabilities, while increasing the level of validity as well as reduced corporate debt offset rising corporate assets